1994
DOI: 10.1210/jcem.78.6.8200936
|View full text |Cite
|
Sign up to set email alerts
|

Altered responses to hypoglycemia of healthy elderly people.

Abstract: Many elderly people are treated with medications or are subjected to diseases which can cause hypoglycemia. We conducted the following studies to assess whether alterations in counterregulatory hormone release, decreased awareness of warning symptoms or alterations in psychomotor performance might increase the susceptibility of the elderly to hypoglycemia. Healthy, nonobese young (n = 10, age < 30) and old (n = 9, age > 65) subjects underwent paired hyperinsulinaemic clamp studies (insulin infusion rate 60 mU/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 24 publications
4
39
0
2
Order By: Relevance
“…Aging has an impact on counter-regulation (5,6). In healthy older adults without diabetes, glucose counter-regulation by glucagon as well as growth hormone and epinephrine responses to hypoglycemia are impaired through the physiology of aging, effectively muting the autonomic process, which would have produced symptoms in the patient (3,5).…”
Section: Age-related Compromise Of the Adaptive Responsive To Hypoglymentioning
confidence: 99%
See 1 more Smart Citation
“…Aging has an impact on counter-regulation (5,6). In healthy older adults without diabetes, glucose counter-regulation by glucagon as well as growth hormone and epinephrine responses to hypoglycemia are impaired through the physiology of aging, effectively muting the autonomic process, which would have produced symptoms in the patient (3,5).…”
Section: Age-related Compromise Of the Adaptive Responsive To Hypoglymentioning
confidence: 99%
“…In healthy older adults without diabetes, glucose counter-regulation by glucagon as well as growth hormone and epinephrine responses to hypoglycemia are impaired through the physiology of aging, effectively muting the autonomic process, which would have produced symptoms in the patient (3,5). Glucose is not properly secreted when its levels fall, which represents loss in pancreatic, renal and hepatic processes.…”
Section: Age-related Compromise Of the Adaptive Responsive To Hypoglymentioning
confidence: 99%
“…However, when hypoglycemia occurs, it powerfully elicits sensations of hunger in young adults. In contrast, even healthy older adults have a broader range over which circulating glucose is maintained and in addition have attenuated counterregulatory responses and delayed recovery from hypoglycemia (85,99,100). Melanson et al (95) recently reported persistently elevated postprandial glucose and insulin in the older women following consumption of 2,092-and 4,184-kJ test meals compared with younger women.…”
Section: Glucose and Insulin As Potential Mediators Of Impaired Rementioning
confidence: 99%
“…Several studies have shown that even though hormonal counterregulation was similar in healthy young and elderly men, elderly men had reduced symptoms at a given hypoglycemia level, suggesting impaired end-organ sensitivity to counterregulatory hormones [ 26 ]. In contrast, other studies found a signifi cant decrease in counterregulatory hormones in healthy elderly men compared with young men, with similar symptom responses [ 27 ]. Healthy elderly subjects also have decreased insulin clearance compared with young, healthy individuals [ 28 ], which may pose a problem in elderly patients using exogenous insulin or secretagogues.…”
Section: Risk Factors For Hypoglycemia In Patients With Diabetes and mentioning
confidence: 94%